2019
DOI: 10.1016/j.jlumin.2019.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Single dot photoluminescence excitation spectroscopy in the telecommunication spectral range

Abstract: Single dot photoluminescence excitation spectroscopy provides an insight into energy structure of individual quantum dots, energy transfer processes within and between the dots and their surroundings. The access to single dot energy structure is vital for further development of telecom-based quantum emitters, like single photon sources or entangled pair of photons. However, application of single dot photoluminescence excitation spectroscopy is limited mainly to dots emitting below 1 µm, while nanostructures op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Both these values correspond well with the energy difference between the excited and ground quantum dot states expected from the measurements on an ensemble of similar QDs. 19) The linewidths of the PLE maxima are relatively broad (~2 meV), which may be related to the relatively large excitation laser linewidth (~0.7 meV) 18) or can result from a complex energy structure (i.e. dense ladder of states) of the QD excited states.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both these values correspond well with the energy difference between the excited and ground quantum dot states expected from the measurements on an ensemble of similar QDs. 19) The linewidths of the PLE maxima are relatively broad (~2 meV), which may be related to the relatively large excitation laser linewidth (~0.7 meV) 18) or can result from a complex energy structure (i.e. dense ladder of states) of the QD excited states.…”
mentioning
confidence: 99%
“…For the identification of excited state in these quantum dots there was used single-dot photoluminescence excitation (PLE) spectroscopy adapted to the spectral range above 1 µm. 18) QDs were excited by a self-made continuous wave external-cavity tunable laser followed by a short-focallength monochromator and shortpass filters to provide a clean excitation laser line. For the nonresonant excitation a 639 nm semiconductor laser was used.…”
mentioning
confidence: 99%
“…During this, the material, mainly from their tops, becomes mixed into the top barrier material layer. Very recently, microphotoluminescence excitation 25 studies of such InAs/InP QDs showed that they possibly have a peculiar feature, namely, that the s – p -shell splitting for excitons in such systems may follow dependence on emission energy, which is opposite to the standard increasing one 26 . There was a single report on similar behavior of InAs/GaAs QDs with a strain-reducing layer, which was attributed to a strong variation of average In content within QD ensemble with a specific form of composition gradient within a QD 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Here, we use an experimental setup built for PLE studies of single nanostructures (µPLE) emitting in the infrared [31], especially in the third telecom window. We successfully probe the spectrum of optically active excited states of C-band-emitting QDs elongated above 100 nm, including individual bright states forming the exciton fine structure, and the negatively charged exciton (X − ).…”
mentioning
confidence: 99%